Parenting Strategies to Develop Pre-Literacy Skills In Early Childhood: A Study In Ngada Regency - Fono, Yasinta Maria; Ngura, Elisabeth Tantiana (Program Studi Magister Pendidikan Anak Usia Dini, 2026)
Pre-literacy is a fundamental foundation for early childhood academic development; however, delays in its acquisition remain common due to limited stimulation in the home environment. This study aims to explore effective parenting strategies to support pre-literacy skills in children aged 4–6 years. Using a qualitative phenomenological approach, the study was conducted in Ngada Regency, Indonesia, involving 15 parents as participants. Data were collected through interviews, observations, and documentation. The findings reveal that democratic parenting through shared reading, storytelling, and daily conversations significantly supports children’s vocabulary development, letter recognition, and early communication skills. Supporting factors include active parental involvement and access to reading materials, while constraints involve limited parental time and low awareness of verbal interaction importance. This study highlights the importance of integrating pre-literacy practices into daily parenting routines to strengthen early literacy development in Indonesian family contexts.